PEMOTONGAN, PENYETORAN, DAN PELAPORAN PAJAK PENGHASILAN DI FKIP UNIVERSITAS SEBELAS MARET - Ngadiman Ngadiman (Universitas Negeri Yogyakarta, 2008)
The aims of this research are to know: ( 1) amputation mechanism, endorsement, andreporting of Income Tax in FKIP UNS ( 2) resistance in executing amputation, endorsement andreporting [of] Income Tax [in] FKIP UNS. According to target of this research hence thisresearch use the descriptive method qualitative. Type of is source of data used in this researchcover the informan, observation and event. this Research data is obtained with the observationtechnique, circumstantial interview, and documentation. This research represent the researchqualitative, hence technique cuplikan used more selective having the character of that isemphasized at the quality of the understanding of information to accurate problems. Frominferential research result 1) crosscut production of PPh Section 21 in FKIP UNS can begrouped to become the: salary, honorarium, functional allowance, overtime DIK.S, to faction IIIto to the 2) PPh Section 21 which have been cut to Exchequer pass the BNI Branch the slowestUNS date of 10 next month;moon takwim. Reporting PPh section 21 conducted by Head OfficeUNS, FKIP only as Owner of Advanced Money Work The ( PUMK) 3) Amputation PPh section22 conducted by treasurer FKIP that is at the time of conducting payment for the buying ofgoods and service to its client. Endorsement PPh Section 22 this conducted by treasurer FKIP[of] while reporting Bursar of DIK.S of Head Office UNS. As does PPh Section 21 bursar FKIPonly as Owner of Advanced Money Work The ( PUMK ) 4) Amputation PPh section 23conducted by treasurer FKIP that is at the (time) of [doing/conducting] payment to service giverTaxpayer. Endorsement PPh Section 23 this conducted by treasurer FKIP, while reportingBursar of DIK.S of Head Office UNS, bursar FKIP only as Owner of Advanced Money Work the( PUMK) 5) Execution of Amputation and reporting PPh Section 21, PPh Section 22 and PPhSection 23 in general no resistance.